2012
DOI: 10.1002/cncr.27770
|View full text |Cite
|
Sign up to set email alerts
|

Hurthle cell carcinoma

Abstract: BACKGROUND: Hurthle cell carcinoma (HCC) is an uncommon and more aggressive thyroid cancer. To date, there is a paucity of data at a population level. In this study, demographic, clinical, and pathologic characteristics of HCC were investigated and compared with other types of differentiated thyroid cancers (ODTCs). The authors also evaluated disease‐specific survival and compliance with American Thyroid Association (ATA) management guidelines from 2009. METHODS: The Surveillance, Epidemiology, and End Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 20 publications
6
58
0
Order By: Relevance
“…HCT is quite rare among differentiated thyroid carcinoma and analysis on large scale is difficult even in large database as SEER [8,11,21]. In fact, biases due to interpretation of histological findings (HCT to be follicular tumor or follicular variant of papillary carcinoma) and manipulation of data may determine different results on the same searched outcomes, as well as demonstrated by three different US study performed on the same database [8,11,21]. In our study, age, sex and size of HCT were comparable to those observed in the literature [7-11, 21, 28-32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HCT is quite rare among differentiated thyroid carcinoma and analysis on large scale is difficult even in large database as SEER [8,11,21]. In fact, biases due to interpretation of histological findings (HCT to be follicular tumor or follicular variant of papillary carcinoma) and manipulation of data may determine different results on the same searched outcomes, as well as demonstrated by three different US study performed on the same database [8,11,21]. In our study, age, sex and size of HCT were comparable to those observed in the literature [7-11, 21, 28-32].…”
Section: Discussionmentioning
confidence: 99%
“…Cytological study subsequent to fine needle biopsy can identify the presence of oncocytic tumor cells, but does not distinguish benign from malignant tumors even though 30 % of HCT are malignant [2,5,6]. In the current literature, Hürthle cell carcinoma (HCC) represents 3-7 % of all thyroid carcinomas [2,7,8]. HCC has a more aggressive behavior compared to the other differentiated thyroid cancer, with a reduced disease-specific survival rate [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with minimally invasive carcinomas usually experience a beter prognosis [73]. Overall, older patients and those with larger tumor size, extrathyroidal extension, and not undergoing surgery have reduced survival [74]. A previous study indicated that in patients with widely invasive HCC, stages III-IV are independent risk factors for recurrence or death.…”
Section: Diagnosis and Management Of Head And Neck Cancermentioning
confidence: 99%